Pump wisdom : problem solving for operators and specialists - Bloch, Heinz P., 1933- (Wiley, 2011)
"PUMP WISDOM was compiled to explain elusive failure causes. Some have to do with pump selection, others have to do with overlooked installation criteria or are simply the result of small deviations that add up. In other words, while a certain assembly dimension may be allowed to reach a defined upper limit, allowing another, and yet another deviation to reach its upper limit on the remaining pump components will lead to operation in a vulnerable region where frequent failures occur. This book sheds light on the issue and, quite unlike any other condensed text, shows exactly what to do so centrifugal process pumps don't fail again"--Provided by publisher